Bioinspired Pyrano[2,3-f]chromen-8-ones: Ring C-Opened Analogues of Calanolide A: Synthesis and Anti-HIV-1 Evaluation - Igor A. Khalymbadzha; Ramil F. Fatykhov; Ilya I. Butorin; Ainur D. Sharapov; Anastasia P. Potapova; Nibin Joy Muthipeedika; Grigory V. Zyryanov; Vsevolod V. Melekhin; Maria D. Tokhtueva; Sergey L. Deev; Marina K. Kukhanova; Nataliya N. Mochulskaya; et al. (Biomimetics, 2024)
We have designed and synthesized a series of bioinspired pyrano[2,3-f]coumarin-based Calanolide A analogs with anti-HIV activity. The design of these new calanolide analogs involved incorporating nitrogen heterocycles or aromatic groups in lieu of ring C, effectively mimicking and preserving their bioactive properties. Three directions for the synthesis were explored: reaction of 5-hydroxy-2,2-dimethyl-10-propyl-2H,8H-pyrano[2,3-f]chromen-8-one with (i) 1,2,4-triazines, (ii) sulfonylation followed by Suzuki cross-coupling with (het)aryl boronic acids, and (iii) aminomethylation by Mannich reaction. Antiviral assay of the synthesized compounds showed that compound 4 has moderate activity against HIV-1 on enzymes and poor activity on the cell model. A molecular docking study demonstrates a good correlation between in silico and in vitro HIV-1 reverse transcriptase (RT) activity of the compounds when docked to the nonnucleoside RT inhibitor binding site, and alternative binding modes of the considered analogs of Calanolide A were established.